Producing Sacred Space in Secular Kitchens: South Asian Immigrant Women’s Hindu Shrines in American Domestic Architecture - Sahney, Puja (Material Culture Review / Revue de la culture matérielle, 2019)
This paper demonstrates the processes of spatial production achieved through the setup of a home shrine by newly arrived Hindu immigrant women inside American houses, particularly the kitchens. By focusing on the home shrine, the paper uses a gendered lens through which to understand vernacular architecture, since women often garner greater control over domestic objects and interiors than they do over construction of buildings. I propose that production of sacred space, achieved through domestic objects like home shrines, is a fluid process. Its location in the house can be more easily changed from one place to another. Compared to the permanent construction of buildings, this compliancy of form may appear less concrete for providing objective architectural analysis. However, I suggest that it is the opposite. The flexibility involved in women’s production process makes room for greater spatial negotiation and demonstrates the diversity of ways concrete domestic architecture is maneuvered to satisfy women’s religious needs over time. Further, the paper demonstrates the wide array of complex decisions that women have to make regarding body movements in the house and worship practices, achieved through material intervention, that speak of domestic architecture in less static and more dynamic ways. By tracing women’s experiences with domestic architecture as new arrivals in the country, and later, as permanent residents, the paper foregrounds women’s strong architectural contributions through the use of domestic objects that enable a gendered and consequently a more inclusive approach to the study of architectural space.